2021
DOI: 10.21577/0103-5053.20210082
|View full text |Cite
|
Sign up to set email alerts
|

Spondias purpurea L. Stem Bark Extract: Antioxidant and in vitro Photoprotective Activities

Abstract: Plant phenolic extracts are widely recognized as an important source of natural antioxidant substances and potential compounds for cosmetic formulations. This study aimed to evaluate the chemical profile, photoprotective and antioxidant activities of stem bark extract of Spondias purpurea L. (ciriguela) and its application in photoprotective formulations. Thirty phenolic constituents were annotated by ultra-performance liquid chromatography coupled with an electrospray ionization quadrupole time-of-flight mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Other studies have shown the presence of important bioactive compounds in Spondias sp. such as ellagic acid [ 6 ], gallic acid, catechin, chlorogenic acid, caffeic acid [ 26 ], and isoquercetin [ 27 ], though these are in lower concentrations.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have shown the presence of important bioactive compounds in Spondias sp. such as ellagic acid [ 6 ], gallic acid, catechin, chlorogenic acid, caffeic acid [ 26 ], and isoquercetin [ 27 ], though these are in lower concentrations.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Flavonoids, tannins [ 33 ], methylgallate, gallic acid, geraniin, sucrose quercetin, vanillicacidO-hexoside, ellagic acid, and salicylicacid, among other compounds, were found in Spondias dulcis leaves and stem bark [ 26 ]. Gallic acid, methyl gallate, digallic acid, and ethyl gallate were isolated from stem bark extract of Spondias purpurea [ 6 ] and rutin and nicotiflorin were isolated from Spondias purpurea pulp [ 7 ]. Palmitic acid, stearic acid, oleic acid, linoleic acid [ 27 ], gallic acid, and flavonoid [ 9 ] were isolated from Spondias tuberosa seeds and leaves.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro sun protection factors of Ba-MeOH crude extract and Ba-BuOH fraction and Apigenin-It is well reported that according to ANVISA (National Health Surveillance Agency of Brazil), the minimum value of SPF for photoprotective products is 6[39], however the FDA (Food and Drug Administration of the United States) recommended that only SPF values that are greater than or equal to 15 are suitable for use in preparations with photoprotective effect…”
mentioning
confidence: 99%